A Agronomia e o Desenvolvimento Sustentável: Por uma Ciência da Complexidade - Benedito Silva Neto (Desenvolvimento em Questão, 2009)
The hegemonic conception of Agronomy has shown increasing difficulties in dealing with the complexity of the problems generated by the current pattern of development of agriculture. From an interpretation of the concept of paradigm based on Critical Realism, which seeks to exempt such a concept of elements of irrationality, the article discusses the possibilities of a paradigm shift in Agronomy. The discussion stresses that the Theory of Complexity and Critical Realism can provide consistent theoretical and epistemological bases for the formation of Agronomy as one of the "sciences of complexity." Thus, according to the Theory of Complexity, the consideration of agriculture as an activity constitutive of open systems is of fundamental importance for the possibility of Agronomy contributes effectively to the promotion of sustainable development. However, for that the hegemony exercised by positivism on Agronomy must be overcome. Therefore, the contributions of Critical Realism in this field are considered of fundamental importance. From these considerations, it is made the characterization of the hegemonic paradigm in Agronomy, called the Normal Agronomy, and the existing elements of a new paradigm, that of Agronomy as a science of complexity. Finally, the article emphasize that the discussion of the concept of paradigm developed indicates that, beyond a purely academic debate, this change in Agronomy is included in the broader field of the social correlation of forces and conflicts of interest. The formation of Agronomy as a science of complexity is, therefore, in an activity essentially emancipatory.